Greenhouse crops of radish under organomineral fertilization sources in the Brazilian semiarid region - Gondim, Ancélio Oliveira; Lira, Renato Pereira de; Pereira, Francisco Hevilásio Freire; Oliveira Neto, Hélio Tavares de; Silva, Francisco de Assis da; Lima Neto, Joaquim Vieira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
The cultivation of radish in an organic system has potential for production to such a degree that alternatives of cultivation have been used to improve productivity in relation to fertilization. Therefore, the objective of this work was to evaluate the effect of organomineral fertilization on gas exchange, growth, and production of radish. The experiment was carried in non-climatized greenhouse crop, with a metallic structure in form of arc, covered with 150 mm low-density polyethylene, in greater length-oriented East-Oste direction of Science and Technology Center of Federal University of Campina Grande, using the Crimson Gigante variety. The soil used experiment was fluvic neosol. The experimental design used was the completely randomized with three replications, using the Crimson Gigante variety. Seven treatments were used, which consisted of three doses of cattle manure (37.5; 75.0, and 150g per pot), three concentrations of biofertilizer (5; 10 and 15%), and mineral fertilization. This work analyzed the characteristics of growth, production, and gas exchange. The treatment (5% biofertilizer) provided greater height of the radish plants, however, the (75.0g manure per pot) resulted in a higher number of leaves. The concentration of 10% of the biofertilizer, obtained the largest diameter, fresh and dry matter of the tuberous root. The treatment presented higher fresh and dry matter of the leaves when compared with the other treatments. The use of organic fertilizers promoted greater production in the radish crop and can be used as an alternative to conventional fertilization.